The Water-Energy-Food-Ecosystem Nexus in the Mediterranean: Current Issues and Future Challenges - De Roo, Ad; Trichakis, Ioannis; Bisselink, Berny; Gelati, Emiliano; Pistocchi, Alberto; Gawlik, Bernd (Frontiers in Climate, 2021)
The Mediterranean is an area where the balance between water demand and abstractions versus water availability is often under stress already, as demonstrated here with the Water Exploitation Index. In this work, model estimates on how different proposed measures for water resources management would affect different indicators. After a review of the current water resources status in the Mediterranean and the definition of indicators used in this study, aspects interlinked with water in the Water-Energy-Food-Ecosystems Nexus are briefly discussed, focusing on problems linked with water scarcity and depletion of groundwater resources as well as with climate change projections. Subsequently, the proposed measures for water efficiency are detailed - irrigation efficiency, urban water efficiency, water reuse and desalination - that might be effective to reduce the growing water scarcity problems in the Mediterranean. Their effects that result from the LISFLOOD model, show that wastewater reuse, desalination and water supply leakage reduction lead to decreased abstractions, but do not affect net water consumption. Increased irrigation efficiency does decrease consumption and reduces abstractions as well. We deduct however that the current envisaged water efficiency measures might not be sufficient to keep up with the pace of diminishing water availability due to climate change. More ambition is needed on water efficiency in the Mediterranean to keep water scarcity at bay.